Comparison of long-term outcomes between ferric sulfate pulpotomy and indirect pulp therapy in primary molars - Ruei-Ren Fang; Kuei-Yuan Chang; Yai-Tin Lin; Yng-Tzer J. Lin (Elsevier, 2019)
Background/purpose: There is no long-term study on the comparison of indirect pulp therapy with ferric sulfate pulpotomy in primary molars. This retrospective study aimed to compare the success rates of ferric sulfate pulpotomy with those of indirect pulp therapy in primary molars during a 4-year follow-up. Material and methods: A total of 114 primary molars from 38 children (16 females and 22 males) with deep carious lesions were selected. Among these molars, 71 indicated for ferric sulfate pulpotomy and 43 indicated for indirect pulp therapy were treated under general anesthesia according to a standard protocol by two senior pediatric dentists. Clinical and radiographic assessments for determining success rates were performed using established criteria at initial, post-operatively, and at 24 and 48 months. Data were analyzed using Fisher's exact test to compare success rates of ferric sulfate pulpotomy and indirect pulp therapy at the 24- and 48-month follow-ups. Results: The overall success rates for indirect pulp therapy and ferric sulfate pulpotomy were 100% (43/43) and 91.5% (65/71), respectively, at the 24-month follow-up; the difference was not significant (P = 0.08). However, the success rate for indirect pulp therapy (93.0%, 40/43) at the 48-month follow-up was significantly higher than that for ferric sulfate pulpotomy (70.4%, 50/71) (P = 0.008). Conclusion: Indirect pulp therapy showed a significantly higher success rate at the 4-year follow-up than did ferric sulfate pulpotomy for treating deep carious lesions in primary molars. Earlier exfoliation was observed after treatment with ferric sulfate pulpotomy compared to indirect pulp therapy. Keywords: Ferric sulfate, Indirect pulp therapy, Pulpotomy